Multicast routing protocol for advanced vehicular ad hoc networks - Omar Saeed Al Mushayt; Wajeb Gharibi; Nasrullah Armi (Universitas Ahmad Dahlan, 2019)
Transport sector has great impact on our daily life. Despite the huge number of vehicular models, driving process still faces many challenges due to the lack information about the roads and the surrounding sudden events, which can result in high number of accidents globally and especially in Saudi Arabia. A new technology, vehicular ad hoc networks (VANETs), has emerged to support Intelligent Transport System (ITS) and to offer advanced solutions for drivers to avoid different hazard events that occur on the road. In this paper, we discuss the multicast and broadcast communications in VANETs, Quality of Sevice (QoS) awaregroup addressing/managing solutions to VANETs which help inclassifying different application that explore and design a new cross-layer framework, aware of high mobility and efficiency.